Identification of Destination's Attributes in Desa Coklat Bali as Educational Tourism Destinations in Tabanan Regency - Agustina Riski, Gusti Ayu; Wulandari, Gusti Ayu (Jurnal Manajemen Pelayanan Hotel, 2022)
The purpose of this study is to identify the destination's qualities in Desa Coklat Bali as an educational tourist destination in Tabanan Regency, based on the 6A Buhalis concept, which stands f or Attraction, Accessibility, Amenities, Ancillary System, Available Packages, and Activities. Data are gathered through interviews, observations, and documentation as part of a descriptive qualitative research methodology. Interviews were held with the Desa Coklat Bali management. To obtain f indings, data were processed using data reduction. The results show that Desa Coklat Bali has implemented attribute 6A for a tourism destination into practice. Desa Coklat Bali is one the educational tourist sites in Bali, which provides tour packages that cover everything f rom the introduction of knowledge about chocolate f arming (Chocolate Tour) to the method of manufacturing chocolate (Chocolate making). The attraction in Desa Coklat Bali is special since it of fers education on cocoa growing and management together with a variety of other activities and packages, including a Rice Plantation Experience, Chocolate Tour, and Chocolate Making. Accessibility and supporting amenities and services might be rated as good. Keywords: Educational Tourism, Destination Attributes, Desa Coklat Bali